2005
DOI: 10.1186/cc3879
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Severe acute renal failure (sARF) is associated with considerable morbidity, mortality and use of healthcare resources; however, its precise epidemiology and long-term outcomes have not been well described in a non-specified population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
163
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(176 citation statements)
references
References 41 publications
8
163
0
5
Order By: Relevance
“…[3][4][5] Despite substantial advances in renal replacement therapy and health care delivery, morbidity and mortality rates associated with AKI have remained high. However, our current understanding of the epidemiology of AKI and its impact on morbidity, mortality, cost of medical care, and development of Chronic Kidney Disease (CKD) is based almost exclusively on studies of patients who developed AKI while hospitalized (HA-AKI).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Despite substantial advances in renal replacement therapy and health care delivery, morbidity and mortality rates associated with AKI have remained high. However, our current understanding of the epidemiology of AKI and its impact on morbidity, mortality, cost of medical care, and development of Chronic Kidney Disease (CKD) is based almost exclusively on studies of patients who developed AKI while hospitalized (HA-AKI).…”
Section: Introductionmentioning
confidence: 99%
“…1,4,[46][47][48][49][50][51][52][53][54][55][56] Despite the trend of lower mortality in recent years, AKI still remains an important negative prognostic factor, particularly in critically ill patients. Even small isolated increases in serum creatinine levels have an associated increase in short-term morbidity and mortality and in longer-term outcomes, including 1-year mortality; 38,48,[57][58][59][60][61][62] this is even more the case when RRT is required. 5,6,13,34,63 A study from the Medicare Sample Beneficiary Analytical File from 1992 to 2001 found that patients with AKI who required RRT had an in-hospital mortality rate of 32.9%, compared with 27.5% in patients with AKI not requiring RRT, and 4.6% in patients without AKI.…”
Section: Outcomes Of Acute Kidney Injurymentioning
confidence: 99%
“…CKD or comorbid conditions leading to CKD are risk factors that predict dialysis dependence following AKI. 61,62 Wald et al 72 looked at outcomes of chronic dialysis and death in AKI patients requiring in-hospital dialysis who survived free of dialysis for at least 30 days after discharge, from a 10-year cohort of all adult patients in Ontario, Canada. Patients with AKI were three times more likely than those without AKI to require chronic dialysis.…”
Section: Outcomes Of Acute Kidney Injurymentioning
confidence: 99%
“…Recent studies would suggest the incidence is far greater than previously appreciated. Observational data have shown that AKI occurs in an estimated 36–67% of all ICU patients [1,2,3], while AKI severe enough to warrant commencement of renal replacement therapy (RRT) occurs in 4–6% [4,5,6]. Moreover, numerous investigations have now shown the incidence of AKI continues to rise [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous investigations have now shown the incidence of AKI continues to rise [7,8,9]. This high and increasing burden of AKI also remains associated with an unacceptably high morbidity and mortality [5, 6,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%